a₁ = 4.2
aₙ = 52.2
sₙ = 366.6
Using the formulars
aₙ = a₁ + (n-1) d
52.2 = 4.2 + (n-1)d ------------------------(1)
Also,
![S_{n\text{ }}=(n)/(2)\lbrack2a_1\text{ + (n-1)d\rbrack}](https://img.qammunity.org/2023/formulas/mathematics/college/ooyz2vuedwjybf9r1b8dfm9s6v8gnmy76t.png)
![366.6=(n)/(2)\lbrack2(4.2)\text{ + (n-1)d \rbrack}](https://img.qammunity.org/2023/formulas/mathematics/college/52td298i25p1wii3fmx5b55roe9xv8kf8o.png)
![366.6\text{ =}(n)/(2)\lbrack8.4\text{ + (n}-1)d\text{ \rbrack}](https://img.qammunity.org/2023/formulas/mathematics/college/l6fpp0urrrvgez850hrqkc9l55zt1pl77v.png)
From equation(1), 52.2 - 4.2 = (n-1)d, this implies; (n - 1)d = 48
substitute (n-1)d = 48 in the above
![366.6\text{ =}(n)/(2)\lbrack8.4\text{ + 48\rbrack}](https://img.qammunity.org/2023/formulas/mathematics/college/r9ideur2ayuntw54w7zvslb3ua75rwo5i5.png)
![366.6\text{ =}(n)/(2)(56.4)](https://img.qammunity.org/2023/formulas/mathematics/college/grmwwmjomvh4nauxyetfo157g0abmixhg1.png)
Multiply both-side by 2
733.2 = 56.4 n
Divide both-side of the equation by 56.4
n = 13
Hence, the number of term is 13